DEVELOPMENT AND PRACTICAL APPLICATION OF COMPUTER TECHNOLOGY IN LANGUAGE EDUCATION - Eshmamatova Mahliyo (Web of Journals Publishing, 2025)
The development of computer technologies is becoming widespread in the field of education. Computer technologies are distinguished by the main didactic principles of the educational process. The use of ICT in educational practice is determined by the rapid development of modern society. Their important advantage is the ability to deliver and store information. Smart planning of lessons with the help of a computer; - the teacher should remain the main source of knowledge and information by organizing, directing and controlling the entire educational process.
Keywords: Computer technologies, language teaching, education